1969
DOI: 10.1103/physrev.182.1607
|View full text |Cite
|
Sign up to set email alerts
|

Nonstatic Relations between Magnetic Moments in the Quark Model

Abstract: Relations between baryon magnetic moments are derived which are independent of orbital corrections, relativistic corrections, and two-body exchange corrections (and generally any two-body correction) in the quark model, provided that the wave-function contributions leading to these corrections are SZ7^-symmetric. Among the relations derived are M(S~)+3/I(S°) = 6/X(A)+2JU(S + )-3fi(p)-/*(») (independent of quark moments) and ju (S°) -M (E~) = M (p)+2/x (n) (if Mf l > = -2/*^).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…The first relation of isovector (12) and the isoscalar relation (13) were also obtained in Refs. [20] and [18], respectively. The relations (12), (13) are satisfied at the 10% accuracy level.…”
Section: B Symmetry Breaking Scenariosmentioning
confidence: 99%
“…The first relation of isovector (12) and the isoscalar relation (13) were also obtained in Refs. [20] and [18], respectively. The relations (12), (13) are satisfied at the 10% accuracy level.…”
Section: B Symmetry Breaking Scenariosmentioning
confidence: 99%
“…These non-static effects must break SU(3) symmetry if they are to improve the agreement of magnetic moment predictions with experiment. This can be seen from the disagreement with experiment of the sum rules [4] µ(p) − µ(n) + µ(Σ − ) − µ(Σ + ) + µ(Ξ 0 ) − µ(Ξ − ) = 0 (0.49 ± .05)…”
Section: Introductionmentioning
confidence: 98%
“…Experimentally, this sum-rule is violated by ten standard deviations, the left hand side being equal to (0.49 ± 0.05) µ N . Franklin [12,13] and Karl [14] have shown that the Coleman-Glashow sum-rule is valid beyond the NQM. Franklin noted the validity of this sum-rule under the assumption of "baryon independence" of a given quark moment contribution.…”
Section: Introductionmentioning
confidence: 99%